1996
DOI: 10.1093/ee/25.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Labeling an Egg Parasitoid, Anagrus epos (Hymenoptera: Mymaridae), with Rubidium within an Overwintering Refuge

Abstract: French prune trees provide overwintering habitat for the egg parasitoid Anagrns epos Girault (Hymenoptera: Mymaridae), an important natural enemy of the the grape leafhopper, Erythroneura elegantula Osborn (Homoptera: Cicadellidae). French prune trees were treated with rubidium during the fall of 1991-1993 to assess the potential for obtaining an elemental label in overwintering A. epos. Multiple applications of 5,000-ppm solutions of RbCI to French prune foliage from late August to early October resulted in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
(26 reference statements)
0
23
0
Order By: Relevance
“…Rubidium is a ubiquitous element chemically similar to potassium but usually found at very low concentrations. This similarity allows rubidium to be incorporated into biological systems at moderate levels without harmful effects (Stimmann 1974, Knight et al 1989, Johnson and Reeves 1995 and results in its vertical transmission between trophic levels (Graham et al 1978, Johnson and Reeves 1995, Corbett et al 1996. These properties permit augmentation of background rubidium levels to internally mark plants, herbivores, and natural enemies.…”
Section: Methodsmentioning
confidence: 99%
“…Rubidium is a ubiquitous element chemically similar to potassium but usually found at very low concentrations. This similarity allows rubidium to be incorporated into biological systems at moderate levels without harmful effects (Stimmann 1974, Knight et al 1989, Johnson and Reeves 1995 and results in its vertical transmission between trophic levels (Graham et al 1978, Johnson and Reeves 1995, Corbett et al 1996. These properties permit augmentation of background rubidium levels to internally mark plants, herbivores, and natural enemies.…”
Section: Methodsmentioning
confidence: 99%
“…It was an excellent marker because ingestion of Rb did not have an adverse effect on survival of nymphs at concentrations between 1000 and 5000 ppm, was not immediately excreted and was retained in the tissues at detectable levels for up to two weeks. Rb has also been used in a variety of insect feeding and dispersal studies (Van Steenwyk, 1978;Holbrook et al, 1991;Holbrook, 1995;Corbett et al, 1996;Woods and Streett, 1996 a, b;Coll et al, 1997;Woods et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that the parasitoids fed on diets containing 500 or 1,000 ppm ofRbCI were labeled up to 4 d after emergence. Corbett et al (1996) reported minimal decay of Rb levels in labeled Anagrus epos Girault adults, but this mymarid did not live >72 h after adult emergence.…”
Section: Resultsmentioning
confidence: 89%
“…Parasitoid labeling with Rb was also accomplished by Corbett et al (1996), Jackson et al (1988), Jackson andDebolt (1990), andHopper (1991) with other hymenopteran species, whereas Guillebeau et al (1993) labeled another aphid species.…”
Section: Discussionmentioning
confidence: 99%